Pelatihan Pengelohan Jantung Pisang menjadi Aneka Cemilan untuk Ketahanan Pangan di Desa Alale Kecamatan Suwawa Tengah - Mamuki, Emiliyan; Anwar, Rustam; Antu, Yulinda R. (Madani: Jurnal Pengabdian Ilmiah, 2024)
Abstract : The KKN-PAR activity aims to educate the community in Alele Village, Central Suwawa District to empower the availability of raw materials, with the innovation of banana blossoms to be processed in the form of unique banana blossom snacks, which have the appeal of being a contemporary snack and have economic value. The method used to achieve the objectives is training with participatory learning techniques and mentoring as well as direct practice in the field. This method places participants as both objects and subjects in the training process. This activity involved Field Supervisor Lecturers (DPL), Students, and members of the MSME group. The mentoring techniques and direction of the KKN-PAR program involve partner groups. Furthermore, direct observations at locations by looking at the availability of raw materials for banana blossoms which will be processed in making snacks. Followed by the core activities, namely providing outreach, counseling, and providing direct assistance to the community on how to make processed banana blossoms, packaging techniques and even labeling. It is hoped that this can increase community innovation and creativity so that Alele Village, Central Suwawa District can become a model village in food security.